An Overview on the phytochemical investigation of therapeutic plants (International Journal of Innovative Research in Engineering & Management, 2021)
Phytochemical screening is an important step in detecting  bioactive principles contained in therapeutic plants, and it might  lead to the development of new therapeutics. The main  phytoconstituents of chosen herbal plants were discovered in this  study in order to link their presence to the bioactivities of the  plants. The presence of steroids, alkaloids, flavonoids,  carbohydrates, amino acids, and protein was detected using  conventional techniques during the screening of the plants. The  occurrence of these phytochemicals can be associated with a plant's therapeutic potential. The collecting of plants, the  extraction of active compounds from diverse sections of plants,  and the qualitative and quantitative analysis of phytochemicals  are the primary topics of this article. More research on these  plants is needed to assess their pharmacological potentials,  isolate, describe, and clarify the structures of the bioactive  chemicals that are responsible for their actions, as well as  additional medical applications.
Keywords: Antibacterial; Medicinal; Phytochemical Screening; Qualitative; Quantitative